2014
DOI: 10.1159/000360305
|View full text |Cite
|
Sign up to set email alerts
|

Overweight in Infancy: Which Pre- and Perinatal Factors Determine Overweight Persistence or Reduction A Birth Cohort Followed for 11 Years

Abstract: Background: A considerable proportion of children with early-life overweight attain a normal weight. To recognize infants at risk of persistent overweight, we compared early-life factors of children with a longitudinal pattern of persistent overweight to children with a pattern of overweight in early but not in later childhood. Methods: In 3,550 children participating in a birth cohort that started in 1996/1997 in the Netherlands, body mass index was repeatedly assessed until age 11 and dichotomized into with/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
2
13
0
1
Order By: Relevance
“…In this issue, Van Rossem et al studied 3550 children participating in a birth cohort with repeated measures until age 11 years. [27] They used group-based modeling and showed that children in the category of persistent overweight were more likely to have overweight parents than those in the overweight reduction pattern, while birth weight and breastfeeding did not differ between the two groups of children. [27] In this issue, Twisk asks whether it is necessary to classify subjects into different trajectories to answer research questions.…”
Section: Categorization Versus Characterization Of Individual Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Van Rossem et al studied 3550 children participating in a birth cohort with repeated measures until age 11 years. [27] They used group-based modeling and showed that children in the category of persistent overweight were more likely to have overweight parents than those in the overweight reduction pattern, while birth weight and breastfeeding did not differ between the two groups of children. [27] In this issue, Twisk asks whether it is necessary to classify subjects into different trajectories to answer research questions.…”
Section: Categorization Versus Characterization Of Individual Growthmentioning
confidence: 99%
“…[27] They used group-based modeling and showed that children in the category of persistent overweight were more likely to have overweight parents than those in the overweight reduction pattern, while birth weight and breastfeeding did not differ between the two groups of children. [27] In this issue, Twisk asks whether it is necessary to classify subjects into different trajectories to answer research questions. [28] Even if classification is useful for description, he questions how useful it can be for analytic purposes.…”
Section: Categorization Versus Characterization Of Individual Growthmentioning
confidence: 99%
“…Pryor et al did not identify a persistent overweight trajectory among children followed from 6 months, but children from families with low SES were at higher risk of following a “high rising” BMI trajectory, which diverged at around 3 years [60]. Children overweight in infancy were less likely to resolve their overweight status as they aged into pre-adolescents if they were from lower SES or ethnic minority families [61]. Lower SES [57] and black [59] children were more likely to exhibit late onset overweight or increasing overweight severity [56] than stable normal weight trajectories.…”
Section: Social Differences In Childhood Growth: Results and Gapsmentioning
confidence: 99%
“…Most studies reported estimates from models simultaneously adjusted for numerous risk factors [26, 27, 30, 31, 43, 44, 46, 50, 51, 56, 59-61, 70], or conducted minimally adjusted analysis [41, 42, 48, 49]. In three studies, the primary study aim did not align with our research question [29, 38, 45], but provided findings that informed our research question of social differences of growth.…”
Section: Modifiable Factors Underlying Social Differences In Growtmentioning
confidence: 99%
“…They found that the odds were significantly higher among female offspring compared to males. Recently, researchers using a Netherlands birth cohort found four overweight trajectory groups from birth to 11 years (never overweight, persistent overweight, overweight reduction, and late onset overweight) [136]. They reported that among the persistent overweight group, children were more likely to have overweight parents in childhood compared to the overweight reduction group children.…”
Section: Bmi and Overweight/obesitymentioning
confidence: 99%